LAYANAN BIMBINGAN KELOMPOK TENTANG BERPIKIR POSITIF SISWA KELAS XI MADRASAH ALIYAH KHULAFAUR RASYIDIN SUNGAI RAYA - Nirwana, Nana; Asrori, Muhammad; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research includes about group guidance service about positive thinking of student of class XI Madrasah Aliyah Khulafaur Rashidin Sungai Raya. The problem in this study is how the stage of formation, transition, activity, termination. This study aims to describe and describe the stage of formation, transition, activity, termination. The method in this research is descriptive method with form of research called survey. The subjects of the study were 24 students of active class XI. Techniques and tools used in this study is an indirect communication technique with a questionnaire tool. Based on the data analysis service guidance group about positive thinking every aspect is in good category. At the time of execution of services for different groups in terms of: 1) Creation Stage obtained results 86.90% 2) Transitional Phase results 87.22% 3) Activity Stage 87.16% 4) Phase Ending 86.99%. Based on the description above, in general, group service activities have been successfully performed on students of class XI Madrasah Aliyah Khulafaur Rashidin Sungai Raya. Thus, this group guidance service is suitable to be applied in its class in order to improve positive thinking. Keywords: Group Guidance Services, Positive Thinking